2022
DOI: 10.1002/admi.202200779
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Cation–π Interactions with Polyphenols for Super‐Hydrophilic Coatings

Abstract: Inspired by natural channels, graphene oxide membrane has been used to separate metals or solvents due to the different affinity between aromatic group and metal ions. [6] In addition, cation-π interactions have been used for the engineering underwater adhesive materials. [7] Mussel-inspired chemistry has demonstrated its versatility for multifunctional coatings based on the oxidized poly merization of dopamine (DA) and noncovalent interactions. [8] The cation-π interaction is one of the primary forces for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Another type of superhydrophilic coating was prepared on a hydrophobic copper mesh via one-step self-assembly of catechol-containing molecules with cations, where cation−π interactions played a dominant role in the adhesion process. 37 Various catechol-containing molecules, such as dopamine and tannic acid (TA), along with different cations including Na + , K + , and tetramethylammonium (TMA), were examined. It was observed that TA-based coatings displayed lower water contact angles compared to dopamine-based coatings.…”
Section: Biomimetic Materials Based On Cation−π Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another type of superhydrophilic coating was prepared on a hydrophobic copper mesh via one-step self-assembly of catechol-containing molecules with cations, where cation−π interactions played a dominant role in the adhesion process. 37 Various catechol-containing molecules, such as dopamine and tannic acid (TA), along with different cations including Na + , K + , and tetramethylammonium (TMA), were examined. It was observed that TA-based coatings displayed lower water contact angles compared to dopamine-based coatings.…”
Section: Biomimetic Materials Based On Cation−π Interactionsmentioning
confidence: 99%
“…Furthermore, the quaternary ammonium groups in CPHA demonstrated antimicrobial activity, which could effectively inhibit bacterial invasion from the outer side without disrupting the ecological balance of healthy human skin. Another type of superhydrophilic coating was prepared on a hydrophobic copper mesh via one-step self-assembly of catechol-containing molecules with cations, where cation−π interactions played a dominant role in the adhesion process . Various catechol-containing molecules, such as dopamine and tannic acid (TA), along with different cations including Na + , K + , and tetramethylammonium (TMA), were examined.…”
Section: Biomimetic Materials Based On Cation−π Interactionsmentioning
confidence: 99%
“…[11][12][13] This bioglue, based on polyphenols, exhibits robust adhesion by the synergistic interaction of various intermolecular forces, playing a crucial role in enhancing researchers' understanding of interactions in soft materials. [14,15] By learning and imitating this polyphenol-based bioglue, researchers have made progress in synthesizing a range of materials such as nanoparticles, [16,17] hydrogels, [18,19] bioadhesives, [20][21][22][23][24][25] and so on. These advancements have resulted in breakthroughs in high-performance adhesion, antimicrobial properties, and tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%